Unconscious load changer: Designing method to subtly influence load perception by simply presenting modified myoelectricity sensor information - Futami, Kyosuke; Seki, Tomoya; Murao, Kazuya (Frontiers in Computer Science, 2022)
Systems of presenting myoelectricity sensor information allow users to understand the body's load for various purposes, such as medical rehabilitation and sports training. If there is a method to create the psychological phenomenon of unconsciously increasing or decreasing a user's load perception simply by changing how to present the myoelectricity sensor values, it will help design a more effective system. Therefore, we propose a method to manipulate load perception by presenting modified myoelectricity sensor information. The proposed method aims to induce higher or lower load perception by modifying the actual myoelectric value to a higher or lower value. We implemented a prototype system and evaluated our method for the two types of load perception of weight perception and fatigue perception when handling objects. The result showed that most subjects unconsciously increased or decreased their load perception to match the presented myoelectric value, while the minority subjects got the opposite response from the majority subjects. This result indicates the feasibility of user assistance systems that use this phenomenon for a good purpose, such as systems that slightly reduce the load perception during physical activity. On the other hand, this result also indicates the feasibility of systems that use this phenomenon for a bad purpose, such as systems that increase user's fatigue to harm user's activity. This study provides helpful findings for designing and using sensor information presentation systems considering the psychological phenomenon.